(untitled) (Tanzania Medical Journal, 2023)
Background Penoscrotal transposition (PST) is an extremely rare congenital anomaly of the external genitalia, characterized by malposition of the penis in relation to the scrotum. PST can be either complete or incomplete according to the positional exchanges between the penis and scrotum and both forms of PST are generally linked with hypospadias. Incomplete transposition is the common form of this entity, and the penis lies in the middle of the scrotum, but complete transposition, the scrotum almost entirely covers the penis, which emerges from the perineum. Both forms are most often associated with a wide variety of other anomalies. We describe a case of a newborn with complete PST, with other associated malformations. Significance This case study has the aim of identifying missed opportunities of early identification of congenital malformations during antenatal care period, by early imaging and karyotype test. Having knowledge on identified congenital malformations during prenatal period is useful to obtain baseline rates and identify clue to the etiology of condition, which will be helpful to plan ongoing antenatal care. Material and Methods This case study was conducted after obtaining ethical clearance from Training, Research and Consultancy Unit (TRCU) at Muhimbili National Hospital and information was collected through in-depth interview (IDI) with the patient’s mother and health care providers who took care of a deceased baby. Also, other data were obtained in patient case file and pictures that were taken. Informed consent was sought from the mother to agree for interview and to allow pictures of her baby to be used in this case study. Outcome The newborn was transferred to the neonatal intensive care unit for further treatment and passed on after 4 hours. No radiological or laboratory investigations were completed within this time. Recommendations 1. Strengthening of antenatal care services in a primary health facility is a key for positive outcome of pregnancy. 2. Referring hospitals in low-income settings should be strengthened with well knowledgeable radiographers. 3. There is a need of strengthening neonatal ICU by ensuring bedside radiological equipment’s is available also other ICU equipment’s are enough. 4. Learning culture must be strengthened in our institute; if we had good learning culture radiological investigations would have been done to the dead baby for learning purpose to detect if there was any other internal congenital anomaly and other cause of death to this newborn.